P16.02 Predictors of hiv acquisition within 12 months of an hiv negative test in men who have sex with men. (13th September 2015) - Cheung, KT; Fairley, CK; Read, TRH; Denham, I; Fehler, G; Bradshaw, CS; Chen, MY; Chow, EPF
Abstract : Introduction: Studies of risk factors for HIV infection usually ascertain these at the time of diagnosis, when they are subject to multiple biases. This study aimed to identify factors present at the time of the last negative HIV test that could predict the risk of HIV acquisition within the next 12 months among men who have sex with men (MSM) attending a sexual health service in Australia. This may allow prioritisation of MSM for preventive interventions, which are becoming increasingly expensive. Methods: We conducted a retrospective cohort study of MSM attending Melbourne Sexual Health Centre between 1 January 2007 and 31 December 2013 with at least two HIV tests within 12 months. Age, sexual behaviour, and bacterial STI diagnoses were extracted from the date of the last negative HIV test and HIV incidence rate ratios (RR) were calculated for each risk factor. Risk factor prevalence was compared among all MSM and those subsequently infected. Results: Of 14745 MSM, 5262 were eligible, contributing 6525 person-years follow-up. 85 new HIV diagnoses were identified within 12 months of a HIV negative test with an incidence of 1.3 (95% CI: 1.0–1.6) per 100 person-years. Significant associations with subsequent HIV infection were: gonorrhoea at any site (RR: 4.1, 95% CI: 2.3–7.0), chlamydia RR: 3.9 (2.3–6.3), inconsistent condom use RR 2.7 (1.6–4.5), and injecting drugs RR 4.1 (1.7–8.6). Risk factor prevalences in tested MSM compared to those subsequently infected were: any bacterial STI (26% vs. 42%), inconsistent condom use (49% vs. 73%), any significant risk factors (60% vs. 83%). Conclusion: This analysis of a large clinic cohort identified significant predictors of subsequent HIV infection that were present at the last negative HIV test, when preventive intervention would still be possible. These could be used to prioritise MSM for potentially costly interventions. Disclosure of interest statement: We declare no conflict of interest.